2013
DOI: 10.1016/j.jcp.2013.07.033
|View full text |Cite
|
Sign up to set email alerts
|

A novel multiblock immersed boundary method for large eddy simulation of complex arterial hemodynamics

Abstract: Computational fluid dynamics (CFD) simulations are becoming a reliable tool to understand hemodynamics, disease progression in pathological blood vessels and to predict medical device performance. Immersed boundary method (IBM) emerged as an attractive methodology because of its ability to efficiently handle complex moving and rotating geometries on structured grids. However, its application to study blood flow in complex, branching, patient-specific anatomies is scarce. This is because of the dominance of gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…This model is easy to implement, efficient to use, and applicable to fully inhomogeneous turbulent flows[3, 13, 14, 49]. This model gives: νT=CnormalΠg normalΠg=Bβαijαij with…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is easy to implement, efficient to use, and applicable to fully inhomogeneous turbulent flows[3, 13, 14, 49]. This model gives: νT=CnormalΠg normalΠg=Bβαijαij with…”
Section: Methodsmentioning
confidence: 99%
“…The diffusion terms and the sub-grid stress tensor arising from the filtering of the equations are computed using fourth order accurate centered difference schemes. The implementation of the methods were tested and validated in our previous studies[3, 13, 14]. …”
Section: Methodsmentioning
confidence: 99%
“…In the overlapping decomposition methods, which include hierarchical adaptive mesh refinement (AMR) techniques [10,14,67] and overset grids [63,8,64,66,79], the sub-domains have interior points in common. On the other hand, multi-block [46,49,20,4] and patched grid techniques [52,28,9] are examples of non-overlapping decomposition or substructuring methods. An alternative to the domain decomposition techniques (DDM) is the implementation of monolithic structured or unstructured grids [18,7].…”
Section: Introductionmentioning
confidence: 99%
“…Darbandi and Naderi [20] proposed a hybrid multi-block finite volume method and demonstrated that their methodology is flexible in mesh generation and can satisfy the conservation properties through the block boundaries on laminar flows. In the more recent work of Anupindi et al [4] a multi-block approach was combined with an immersed boundary method to perform LES of arterial hemodynamics. In this study, only equal blocks with uniform meshes were utilized to avoid any interpolation at the block-interfaces and make the scheme conservative.…”
Section: Introductionmentioning
confidence: 99%
“…However, with recent developments in immersed boundary methods [25][26][27][28][29][30][31], structured Cartesian grid methods are back in favour. These methods have been extended for a wide variety of flow problems including moving boundary and fluid structure interaction problems [32][33][34][35]. Cartesian grid methods are very easy to parallelize using domain decomposition, and hence, these are especially suited for LES/DNS using massively parallel computers.…”
Section: Introductionmentioning
confidence: 99%